A matemática em um curso de engenharia: vivenciando culturas - Gomes, Gisela Hernandes (2009)
The purpose of this study was to investigate aspects of Mathematics utilized in End-of-program Assessment Papers in Engineering specifically the manner in which students who attend the final terms of Mechanical Engineering and Production Engineering programs in a Brazilian university report the mathematical contents learned during the undergraduate years and which mathematical elements they apply to their End-of program Assessment Papers. Additionally, the investigation attempted to clarify how two cultures that of engineers and that of the Engineering program classroom are revealed in the discourses of students and teachers. The theoretical-methodological background of the study included aspects of mathematical thinking (Schoenfeld, 1992; Cardella, 2006), of the Grounded Theory (Charmaz, 2006; Corbin & Strauss, 2008), and of Video Data Analysis (Powell, Francisco, & Maher, 2004). The findings revealed differences between the culture of engineers and that of the Engineering classroom in aspects such as mathematical rigor versus the use of approximations in the results, in addition to revealing elements of the mathematical thinking present in the assessment papers elements that can be explored in the classroom with the use of modeling and computer software